Strut-and-Tie Method for GFRP-RC Deep Members - Zahid Hussain; Antonio Nanni (International Journal of Concrete Structures and Materials, 2024)
Abstract The current code provisions in ACI 440.11 are based on the flexural theory that applies to slender members and may not represent the actual structural behavior when the shear span-to-reinforcement depth ratio is less than 2.5 (i.e., deep members). The Strut-and-tie method (STM) can be a better approach to design deep members; however, this chapter is not included in the code. Research has shown that STM models used for steel-reinforced concrete (RC) give satisfactory results when applied to glass fiber-reinforced polymer-reinforced (GFRP)-RC members with a/d less than 2.5. Therefore, this study is carried out to provide insights into the use of STM for GFRP-RC deep members based on the available literature and to highlight the necessity for the inclusion of a new chapter addressing the use of STM in the ACI 440.11 Code. It includes a design example to show the implications of ACI 440.11 code provisions when applied to GFRP-RC deep members (i.e., isolated footings) and compares it when designed as per STM provided in ACI 318-19. It was observed that current code provisions in ACI 440.11 required more concrete thickness (i.e., h = 1.12 m) leading to implementation challenges. However, the required dimensions decreased (i.e., h = 0.91 m) when the design was carried out as per STM. Due to the novelty of GFRP reinforcement, current code provisions may limit its extensive use in RC buildings, particularly in footings given the water table issues and excavation costs. Therefore, it is necessary to adopt innovative methods such as STM to design GFRP-RC deep members if allowed by the code.